Poling behaviour of technical ferroelectrics studied by in-situ neutron diffraction - Hoelzel, M.; Hinterstein, M.; Kungl, H.; Jo, W.; Fuess, H. (Видавництво Львівської політехніки, 2012)
Neutron diffraction studies on technical ferroelectric ceramics under the influence of high electric fields were performed to establish correlations between the macroscopic poling behaviour and corresponding structural changes. The investigations were carried out on bulk samples of lanthanum doped lead zirconate titanate (PLZT) with compositions around the morphotropic phase boundary and also on a bismuth sodium titanate based system (BNTBT-KNN). In two compositions of the system BNT-BT-KNN, the large field induced macroscopic strain could be explained by a phase transformation during the poling process. PLZT samples were investigated under various orientations of the electric field to examine domain switching and strain effects.
Keywords: ferroelectrics; neutron diffraction; piezoelectrics